A roadmap to Innovation: The Directed Assembly Network - Rose, Julian; Raithby, Paul; Woods, Jenny; Makatsoris, Harris; Price, Sally; Wilson, Chick; Jackson, George; Ward, Mike; Brammer, Lee; Rosseinsky, Matt; Yaliraki, Sophia; Champness, Neil; et al. (Cranfield University, 2016)
The Directed Assembly Network, an EPSRC Grand Challenge Network, set out in 2010 to build a wide-reaching community of scientists, engineers and industrial members that includes: chemists, biologists, physicists, chemical engineers, mathematicians, and computer scientists, to name but a few. This Roadmap has been constructed by the Network community over years of consultations and continuous engagement through: themed meetings, sandpits, Network awards (proof of concept projects) and strategic meetings. In 2010, the Network was tasked to look 20-40 years into the future, and to capture, short, medium and long term goals. Over the 6 years since its inception the Network has grown to over 1,000 members and hosts several highly acclaimed meetings each year. Early career researchers are at the heart of the Network and benefit greatly from access to, and networking with our world-leading members, senior management team and Network Champions. The Network is now embedded into the culture of the UK landscape and continues to work at the leading edge. The vision of the Network is to be able to control the assembly of matter with sufficient certainty and precision to allow the preparation of materials and molecular assemblies, with far more sophisticated and tuneable properties and functions, than are accessible in materials synthesised using current methods. The UK position and World challenges are set out in this Roadmap to highlight the importance that new materials provide when it comes to solving the Grand Challenges of this century. Challenges include: the development of medicine and implants tailored to each individual; the creation of green alternatives to scarce resources; discovering new energy sources; capturing pollutants; enhancing both crop production & the provision of clean water and developing exciting innovations, such as smart materials, new catalysts, organic computing and high-temperature superconductors that will transform society. The Network has proven very successful in fostering this research, helping to maintain or propel the UK to the forefront of the research areas. £50 Million of subsequent grants are linked to and/or supported by the Directed Assembly Network. The science is set out across 5 overlapping themes in this Roadmap, which encompass directed assembly and disassembly, and the translation and scale-up of the research towards manufacturing. Some examples of the Network-funded proof of concept projects are highlighted, showing advances in the short term goals set out in the 2012 edition of the Roadmap. Areas for potentials calls or signposting, along with fundamental science topics for further development are discussed before structural recommendations are also made. Finally, conclusions and the Network Management team are presented.